PENGARUH ETIKA KERJA, KOMITMEN KERJA DAN PROFESIONALISME KERJA TERHADAP KINERJA KARYAWAN PT. IKA WAHANA MANDIRI - Pramesty Ardea Nur Dianta; Vera Firdaus; Sumartik Sumartik (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research was motivated by the decline in performance of PT Ika Wahana Mandiri since 2020, aiming to analyze the influence of work ethics, work commitment, and work professionalism on employee performance, to provide a more comprehensive understanding of factors affecting performance in the context of private companies in Indonesia. The study employed a descriptive quantitative method with multiple linear regression analysis, involving 75 employees of PT. Ika Wahana Mandiri as a total sample, and used SPSS version 25 for processing primary data from questionnaires and secondary data. The research results concluded that to improve performance, strong work ethics, high commitment, and maintained professionalism are necessary. Good work ethics, such as responsibility and valuing time, contribute significantly to employee productivity. Moreover, strong commitment, reflected in loyalty and pride towards the organization, can encourage employees to put in extra effort for the company's success. High professionalism, supported by competence and responsibility, also plays an important role in improving work quality. Thus, when ethics, commitment, and professionalism are combined in a mutually supportive and reinforcing manner, they will further enhance overall employee performance, create a positive and productive work environment, and help achieve the company's strategic goals.